PEREMPUAN DAN POLITIK PADA MASA AWAL ISLAM (STUDI TENTANG PERAN SOSIAL DAN POLITIK PEREMPUAN PADA MASA RASULULLAH) - Ismail, Zaky (Jurnal Review Politik, 2016)
Islam recognizes the importance of women in both public life and po- litical life by putting women in a honorable political status that reflect their nobility. Based on that argument, this study seeks to understand women’s social and political role in the early days of Islam. Focusing during life time of Prophet Muhammad, this paper tries to elaborate the genuine Islamic perspective on how women social and political rights are constructed. Using historical approach, this paper argues that gener- ally, Arab women’s social political right is poorly recognized by author- ity at that time. This condition emerged because there is no legal norms that can bring them back to the straight path. After Islam came to Arab, women life took a favorable turn. Honor, dignity even social and political right were carefully arranged by authority. Man and women were taught to respect each other both in private and social life.